FACTORS AFFECTING TAXPAYER COMPLIANCE WITHIN THE SCOPE OF LAND AND BUILDING TAX (PBB) IN THE MULYOREJO DISTRICT AREA, SURABAYA CITY - Paramitha Gamma Miswa Aninthia; Yogie Surya Dhanirizka (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
The study aims to analyze the factors that influence taxpayer maintenance within the scope of land and building tax (PBB) in the Mulyorejo sub-district area of Surabaya. The sample in this study consisted of 50 PBB taxpayer respondents. This study uses quantitative methods and data collection procedures are used by administering questionnaires, while the sample uses convenience sampling. The analysis method uses multiple regression analysis. The data quality tests used are Validity Test and Reliability Test. The research show that the variables of taxpayer attitude, taxpayer motivation, and sanctions against taxpayers influence compliance within the scope of land and building tax (PBB) in the Mulyorejo sub-district, Surabaya City